Effect levels energy and protein and type feed on Broiler performance Ross. - Hussein Al-Machi, Abbas Salime (Journal of Kerbala for Agricultural Sciences, 2018)
This experiment aimed to evaluate the replacement of some materials locally available used in the manufacture of feed mixtures instead of pre-prepared imported and used in the production of hens meat, this study was carried out at the Poultry Research Station –department of Karbala agriculture - Karbala Governorate at the period from 15/11/2016 to 27/12/2016 to study the effect change different levels from Energy and Protein and type feed Pellet and Mash in broiler performance, in the experiment, 1200 hens meat was used (ross variety) one day age and weight 42gm.chick-1, Purchased from one of the commercial hatcheries in the province of Karbala, chicks were randomly distributed to four treatments (300 chicks for treatment) with three replicates (100 chicks for replicate) experiment started since first day of age to 6 weeks age, CRD design used to data analysis, the treatments was divided as follows: T1 (control) : broiler feeding by the feed Mash. T2 broiler feeding by the feed Pellet with energy and protein agreeing with Gide Breeding. T3 : T2 broiler feeding by the feed Pellet with level energy and protein like T1 (control) but it is apellet.T4 : T2 broiler feeding by the feed Pellet with low energy of T2 about 50 Kcal and protein like same T2 . The productivity characters were studied included body weight, the increase in weight, feed consumption, feed conversion coefficient of hens, mortality rate, dress percentage, percentage of internal organs weight and percentages of the main and secondary parts of the carcass. The results showed the following: There were significant differences at (P ≤0.01) in rates of live body weight, weight increase, feed consumption increased, percentage of mortality rate, relative weight of the back, The lowest cost of feed was when feeding by T2 treatment.